2013
DOI: 10.1007/s00299-013-1543-x
|View full text |Cite
|
Sign up to set email alerts
|

Albinism in barley androgenesis

Abstract: Androgenesis is highly useful for plant breeding, significantly reducing breeding cycle times, as well as in a wide range of biological research. However, for widespread use this process must be efficient. Despite several decades of research on the phenomenon of androgenesis, many processes involved are obscure and there is much to be understood about androgenesis. One of the problems inherent in androgenesis, and reducing its efficiency, is albinism. This article reviews albinism in barley anthers and microsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 40 publications
2
53
0
1
Order By: Relevance
“…For immature and mature embryo-derived cultures however, albinism is not a common problem. In androgenic cultures of wheat and barley, more than 60-80% of the variations associated with albino plant regeneration is genotype-dependent (Kumari et al 2009, Makowska andOleszczuk 2014). Nevertheless, the recovery of green vs. albino plants in anther cultures of cereals could be improved by optimized regeneration protocols (Kumari et al 2009, Makowska andOleszczuk 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For immature and mature embryo-derived cultures however, albinism is not a common problem. In androgenic cultures of wheat and barley, more than 60-80% of the variations associated with albino plant regeneration is genotype-dependent (Kumari et al 2009, Makowska andOleszczuk 2014). Nevertheless, the recovery of green vs. albino plants in anther cultures of cereals could be improved by optimized regeneration protocols (Kumari et al 2009, Makowska andOleszczuk 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In androgenic cultures of wheat and barley, more than 60-80% of the variations associated with albino plant regeneration is genotype-dependent (Kumari et al 2009, Makowska andOleszczuk 2014). Nevertheless, the recovery of green vs. albino plants in anther cultures of cereals could be improved by optimized regeneration protocols (Kumari et al 2009, Makowska andOleszczuk 2014). In accordance with this assumption, our latest research showed that the changes in culture medium composition, namely of the concentrations/types of plant growth regulators and carbohydrate content, provided a more effective control of somatic embryogenesis and a lower production of albino plants in T. kiharae ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the facts that exogenous stress can drastically reduce the number of plastids in microspores (Caredda et al 2000) and that in plants chilling temperatures can reduce up to 90 % of chlorophyll content (Tewari and Tripathy 1998) all presented data together with significantly higher CAT activity detected in anthers isolated from freshly cut tillers of recalcitrant DH lines in comparison with responsive DH lines ( _ Zur et al 2014) suggest that some level of H 2 O 2 is important not only for microspore reprogramming but also for successful transition from a non-photosynthetic proplastid to a functional chloroplast. Similarly, Makowska and Oleszczuk (2014) concluded that stress is capable of reprogramming a microspores themselves but not necessarily the plastids. This may lead to the production of androgenic embryos containing plastids that follow the gametophytic development, what leads directly to regeneration of chlorophyll-deficient plants.…”
Section: Discussionmentioning
confidence: 99%
“…In order to elucidate the mechanism of albino plant formation researchers have focused on three areas: cytology, plastid genomics and the nuclear genome, identifying numerous factors as involved in control of the process (Makowska and Oleszczuk 2014). It has been revealed that the number of obtained albino plants depends on the pre-treatment used for androgenesis initiation, the composition of induction medium and in vitro culture conditions (Ć alić et al 2013;Immonen and Robinson 2000;Jacquard et al 2009;Lantos et al 2013;Ś lusarkiewicz-Jarzina and Ponitka 1997;Wojnarowiez et al 2002).…”
mentioning
confidence: 99%
“…Also in accordance with their results, a highly negative correlation (ρ = −0.83; P ≤ 0.001) between the number of green plants produced and the percentage of albinos was found, which is expected in the presence of both green and albino plant production promoting alleles in a population (Opsahl-Ferstad et al 1994b). Additionally, the low negative correlation (ρ = −0.29; P ≤ 0.01) between the number of albino plants produced and green plant percentage, suggests that the environment is of greater influence on albino production than genetics (Kumari et al 2009;Makowska and Oleszczuk 2014), even though QTL for albinism have been reported in several cereal species (He et al 1998;Chen et al 2007;Krzewska et al 2015). The presence of alleles required for green plant production can thus be 'phenotypically invisible', if potential green regenerants suffer from environmentally induced albinism.…”
Section: Albinismmentioning
confidence: 99%